Running in the family - Ondaatje, Michael 1943- (New York Vintage Books, 1993)
An autobiographical journey of discovery gathers together fragments of memory, experience, and family history in order to understand the meaning of his parents' legacy and his own heritage.
Originally published in hardcover
Keywords: Ondaatje, Michael -- 1943- -- Childhood and youth; Authors, Canadian -- 20th century -- Biography; Sri Lanka -- Biography